Identifying the Determinants and Effects of Education Based on the Hidden Curriculum Theory - Żłobicki, Wiktor (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The hidden curriculum concept is an example of an interdisciplinary approach in which educational processes were analysed from a sociological perspective. It turns out that education is not neutral to political, economic, social, and cultural influences. This results in the emergence of phenomena that disrupt the teaching and learning process in the entire education system, not excluding kindergartens, schools of all types and universities. As a consequence, we can talk about limiting the subjectivity of man and strengthening in education the tendency to authoritarianism and symbolic violence.
Keywords: education; school; student; teacher; hidden curriculum